NUMERALIA DAN ADJEKTIVA DALAM BAHASA INDONESIA - Tri Indah Kusumawati (Universitas Islam Negeri Sumatera Utara, 2019)
The famous term in Indonesian grammar are numeralia (noun) and adjectiva (adjective). This article disscusses on form and independency, function of adjective based on form, function and usage.Key word : numeralia, adjective, orthograhic, colective, group